(untitled) (CIPEEX, 2026)
Introduction: Osteogenesis imperfecta (OI) is a rare genetic disorder of connective tissue, resulting from mutations in the genes responsible for the synthesis or structure of type I collagen. Characterized by variable bone fragility, it can lead to frequent fractures even after minimal trauma. There are five main types of OI, varying in severity due to different genetic mutations. Objective: To describe a clinical case of type IV osteogenesis imperfecta (OI), highlighting the importance of the differential diagnosis with secondary osteoporosis and discussing the currently available therapeutic approaches. Case Report: Female patient with a history of recurrent fractures since early childhood, short stature, bone deformities, grayish sclerae, and progressive bilateral hearing loss. The patient was referred to the outpatient clinic for osteometabolic diseases for investigation of bone fragility. Genetic testing identified a mutation in the COL1A1 gene, confirming the diagnosis of type IV OI. Treatment included intravenous bisphosphonates, regular physiotherapy rehabilitation, and corrective orthopedic surgeries, with progressive improvement in functional status. The patient remains under multidisciplinary follow-up, focusing on fracture prevention, promotion of functional independence, and psychosocial support. Conclusion: This case reinforces the importance of considering OI in the differential diagnosis of patients with recurrent fractures and highlights the role of continuous multidisciplinary follow-up in the clinical management of the disease. Early diagnosis allows for better therapeutic planning and appropriate genetic counseling.